A study of implementation open IMS platform setup- experiences of an IMS testbed / Nurul Izzati Aslaman - Aslaman, Nurul Izzati (2012)
IP Multimedia Subsystem (IMS) is an architectural framework for delivering Internet Protocol (IP) multimedia services. It was introduced by the Third Generation Partnership Project (3GPP) to enable 3G mobile systems to provide ubiquitous cellular access to all the services that the Internet provides, with improved Quality of Service (QoS), appropriate charging and integration of services. It is regarded as the standard service delivery platform for providing multimedia applications in the Next Generation Network (NGN). The main beautiful feature of the IMS is the convergence of fixed and wireless networks to provide vo'ice, data and variety of multimedia services. It provides the opportunity to build open IP based service platform that will enable an easy and efficient deployment of new multimedia communication services mixing voice and data services. As such a testbed is quite complex by its very nature, Fraunhofer Institute (FOKUS), a German organization known as a leading research institute in the field of open communication systems, has coined in addition the notion of technology focused "playgrounds". One of these playgrounds is the "Open IMS Playground @FOKUS". This thesis presents the Study of Implementation Open IMS Platform Setup and would focus to the experiences that will be cover through the implementation of an IMS testbed as well as also provides an overview of the "Open IMS @ FOKUS".